The court fees as variety of the state duty - Rossikhin, Vasyl; Rossikhina, Halyna; Kaganovska, Tetyana; Holovko, Oleksandr; Navrotskyi, Oleksii; Musiienko, Oleh (Chennai : IAEME Publication, 2020)
The article examines the place, role and features of the legal regulation of the court fees. Attention is drawn to the problematic moments and difficult situations in the legislative registration of this concept. The need to correct them is noted and recommendations are given for improving the legal regulation of court fees.
Описка: у віхідному документі надрукована сторінка 1332, а повинна бути -1338.
Keywords: LAW/JURISPRUDENCE; judicial reform; court fees; state duty; claims